TEORI BELAJAR BAHASA - iatun hayatun najmi (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to examine some of the text, script publications and books related to the theory of language learning. Get to know some language learning in learning theory as a theory of behavioristik mangacu to the behaviour of generative theory of nativism, language based on generative theory kognitifisme's talents, which focuses upon the cognitive theory, and kecapan Constructivism is a blend of cognitive and affective. Principles of language learning focuses on learning activities with a series of picture and feelings regularly in the learning process in order to assist students in understanding a problem so what-what is delivered by teachers can be accepted maximum possible by learners. The Scope Of Language Learning Among others listening/focusing on purpose to a voice, speaking/spawned with the feeling, reading to redirect students may know something by way of direct, Writing is an attempt to redirect skilled students composing/arranging language Indonesia well.